Unconsolidated undrained shear strength behaviour Beaufort’s peat soils - Mohd Syeddre Sutarno; Habib Musa Mohamad; Muhammad Aniq Azraei Suradi (GEOMATE International Society, 2025)
Peat soil is a highly organic surface layer primarily derived from plant remains. Peat, on the other hand, refers to the subsurface layer of wetland systems, consisting of unconsolidated superficial layers with a high content of non-crystalline colloids (humus). It is generally dark brown to black in color, has an organic odor, and exhibits a spongy consistency. Peat soil is commonly found in swamp areas and is a partially decomposed organic layer of soil formed from plant matter that accumulates under conditions of waterlogging, high acidity, oxygen scarcity, and nutrient deficiency. Peat soils typically have a low shear strength ranging from 5 to 20 kPa, high compressibility values between 0.9 and 1.5, and a high moisture content exceeding 100%. Additionally, peat exhibits significant deformation, variable magnitudes, and specific structural characteristics, with an organic matter content exceeding 75%. The investigation of peat soil involves Unconsolidated Undrained Triaxial Tests, where parameters are studied under varying effective stresses of 13 kPa, 25 kPa, 50 kPa, and 100 kPa. Samples were collected from three different locations: Kpt-L1, Kpt-L2, and Kpt-L3. The findings indicate that peat soils from different locations yield varying results due to differences in composition. The Unconsolidated Undrained Triaxial Test was conducted on peat soil from Sabah for the first time by a researcher at the Klias Peat Swamp Field Centre in Beaufort, Sabah. Due to the high moisture content of peat soil, the Unconsolidated Undrained and Consolidated Undrained tests are not significantly different in their results.